STRATEGI MANAJEMEN MODERASI BERAGAMA DI LINGKUNGAN SEKOLAH DALAM MEWUJUDKAN HARMONI SOSIAL: A NARRATIVE LITERATUR REVIEW - Witrin Noorjutstiatini; Muliawan, Dadang; Nasrullah, Yufi Mohammad; Latip, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Religious moderation plays a crucial role in maintaining social harmony by promoting tolerance, inclusivity, and balance in religious practices. This study aims to analyze management strategies for implementing religious moderation in schools to foster social harmony. The research employs the Narrative Literature Review (NLR) method by selecting, analyzing, and synthesizing relevant studies on religious moderation strategies in school environments. The research process includes topic selection, reference searching, source selection based on thematic relevance and quality, and narrative synthesis of findings. The results identify three key strategies for managing religious moderation in schools: (1) integrating religious moderation into the school curriculum, (2) strengthening an inclusive and tolerant school culture, and (3) enhancing educators' capacity in religious moderation education. These strategies aim to instill tolerance, respect for diversity, and prevent the spread of extremist ideologies among students. The findings highlight the importance of comprehensive policy implementation to strengthen religious moderation in education